Cybersecurity Leadership Demystified - Ozkaya, Dr. Erdal; Ozkaya, Dr. Erdal; Abdulhayoglu, Melih (Packt Publishing, 2022)
Gain useful insights into cybersecurity leadership in a modern-day organization with the help of use casesKey FeaturesDiscover tips and expert advice from the leading CISO and author of many cybersecurity booksBecome well-versed with a CISO's day-to-day responsibilities and learn how to perform them with easeUnderstand real-world challenges faced by a CISO and find out the best way to solve themBook DescriptionThe chief information security officer (CISO) is responsible for an organization's information and data security. The CISO's role is challenging as it demands a solid technical foundation as well as effective communication skills. This book is for busy cybersecurity leaders and executives looking to gain deep insights into the domains important for becoming a competent cybersecurity leader.The book begins by introducing you to the CISO's role, where you'll learn key definitions, explore the responsibilities involved, and understand how you can become an efficient CISO. You'll then be taken through end-to-end security operations and compliance standards to help you get to grips with the security landscape. In order to be a good leader, you'll need a good team. This book guides you in building your dream team by familiarizing you with HR management, documentation, and stakeholder onboarding. Despite taking all that care, you might still fall prey to cyber attacks; this book will show you how to quickly respond to an incident to help your organization minimize losses, decrease vulnerabilities, and rebuild services and processes. Finally, you'll explore other key CISO skills that'll help you communicate at both senior and operational levels.By the end of this book, you'll have gained a complete understanding of the CISO's role and be ready to advance your career.What you will learnUnderstand the key requirements to become a successful CISOExplore the cybersecurity landscape and get to grips with end-to-end security operationsAssimilate compliance standards, governance, and security frameworksFind out how to hire the right talent and manage hiring procedures and budgetDocument the approaches and processes for HR, compliance, and related domainsFamiliarize yourself with incident response, disaster recovery, and business continuityGet the hang of tasks and skills other than hardcore security operationsWho this book is forThis book is for aspiring as well as existing CISOs. This book will also help cybersecurity leaders and security professionals understand leadership in this domain and motivate them to become leaders. A clear understanding of cybersecurity posture and a few years of experience as a cybersecurity professional will help you to get the most out of this book.